PENDAPATAN DAN RISIKO USAHATANI PADI ORGANIK DAN NON ORGANIK DI KARANGASEM, KETAPANG, SUSUKAN, KABUPATEN SEMARANG - Mayasari Dwi Rahayu; Yuliawati Yuliawati (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2020)
The main commodity of crops that most contributes to agricultural development is rice. The purpose of this research was to determine differences in income, differences in the value of production and income risk, as well as the effect of production factors on the risk of production of organic and non-organic rice farming in Karangasem, Ketapang Village, Susukan District, Semarang Regency. The sampling technique is simple random sampling. Determination of the number of samples with the Slovin formula, obtained 89 farmers as respondents consisting of 44 organic farmers and 45 non-organic farmers. Income differences were analyzed using the average difference test, to determine differences in the value of production risk and income using the coefficient of variation (CV), while to determine the effect of production factors on production risk using multiple linear regression analysis. The results showed that organic rice farming income (Rp. 7,872,844) was greater than non-organic rice farming income (Rp 4,963,953) with a difference (Rp 2,908,891) and was significantly different. Based on the value (CV), the risk of organic rice farming production is 0.27 higher than the value (CV) of non-organic rice farming 0.21. The value (CV) of non-organic rice farming income risk is 1.01 higher than the value (CV) of organic rice farming of 0.85. Production factors that influence the risk of organic rice farming production are labor, and for non-organic rice farming is synthetic fertilizer.